Frequency-dependent ultrasensitive terahertz dynamic modulation at the Dirac point on graphene-based metal and all-dielectric metamaterials. (30th October 2021) - Yao, Haiyun; Yan, Xin; Yang, Maosheng; Yang, Qili; Liu, Yunyun; Li, Aiyun; Wang, Meng; Wei, Dequan; Tian, Zhongjun; Liang, Lanju
Abstract: The development of terahertz (THz) technology is creating a demand for devices that can modulate THz beams. Here, we report the design and characterization of three THz modulators. One uses graphene and a metal-microstructure-integrated metamaterial, another uses a bare graphene film, and the third uses graphene-based all-dielectric metamaterials. Ultrasensitive dynamic THz modulation is achieved by shifting the quasi-Fermi level between the Dirac point, the conduction band, and the valence of graphene via continuous-wave optical illumination or bias voltages. When the Fermi level is close to the Dirac point, the modulation is ultrasensitive to the external stimuli. The modulation depth can reach the maximum value of 346% in the current public publication, breaking through the bottleneck of modulation inefficiency, and is expected to realize practical applications for the first time. For the range 0.2–2 THz, the modulation depth initially increases, then decreases. These results will enable potential designs for ultrasensitive THz devices. Graphical abstract: Image 1